Biomas brasileiros : aproximações para o ensino por investigação através de um guia didático - Erpen, Elaine Beatriz (2022)
This work aims to develop a teaching guide on Brazilian biomes, which serves as a pedagogical tool for the teaching of biology in high school using inquiry-based teaching. The appropriation of knowledge about Brazilian biomes allows students to understand the environmental conditions necessary for the maintenance of life, empowering them to make better decisions regarding the use of natural resources, as well as to propose future development measures that are conscious and ecologically sustainable, expanding the possibilities of effective participation of students as citizens. Through educational actions, the individual develops skills and abilities that can be applied in real life, promoting critical thinking, developing skills that are not limited to theory, but that teach how to act in society and transform it, and inquiry-based teaching for biology education is this tool that allows the learning of concepts and procedures characteristic of science, besides developing important cognitive and social skills and abilities. For the validation of the educational product, high school biology teachers were invited to analyze the material, through Google Forms, and validate its effective use in the classroom as a pedagogical tool for the meaningful learning of this theme through approaches to teaching by inquiry. The didactic guide “Vamos conhecer os biomas brasileiros”, proposes planned and organized activities by investigation, to provide students with the means to use their previous knowledge as a starting point for new ideas, and to raise hypotheses and deepen their knowledge, in a way that enables the teacher to involve, instigate curiosity and keep students interested and participatory, thus developing the capacity for argumentation.